Amino acid composition of soybean seeds as affected by climatic variables - Carrera, Constanza Soledad; Reynoso, Cora Marcela; Funes, Gustavo Javier; Martinez, Maria Jose; Dardanelli, Julio Luis; Resnik, Silvia Liliana (Empresa Brasileira de Pesquisa Agropecuária (Embrapa), 2023)
The objective of this work was to perform a quantitative analysis of the amino acid composition of soybean seeds as affected by climatic variables during seed filling. Amino acids were determined from seed samples taken at harvest in 31 multi‑environment field trials carried out in Argentina. Total amino acids ranged from 31.69 to 49.14%, and total essential and nonessential amino acids varied from 12.83 to 19.02% and from 18.86 to 31.15%, respectively. Variance components expressed as the percentage of total variation showed that the environment was the most important source of variation for all traits, followed by the genotype x environment interaction. Significant explanatory linear regressions were detected for amino acid content regarding: average daily mean air temperature and cumulative solar radiation, during seed filling; precipitation minus potential evapotranspiration, during the whole reproductive period; and the combinations of these climatic variables. Each amino acid behaves differently according to environmental conditions, indicating compensatory effects among them.